Penilaian Mata Pelajaran Bahasa Inggris - Mutiara O Panjaitan (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2010)
The learning process of English subject is designed in line with the way English is used in society in everyday life. Teaching learning activity and assessment are integrated process. It means that assessment executed while learning activity is going on. Based on the investigation on school curriculum it is that learning activity and assessment were designed as separate components and in formal way. The task of assessment does not depict the real word. Besides, teachersâ€™ ability in designing assessment is various that will influence quality of output. Based on this situation it is needed to develop a model of assessment on English subject that could be used as a reference for teacher and stakeholders when developing school curriculum. Language is a tool for communication orally and written. Communication competence or discourse competence is a competence to communicate orally and written as well in certain communication event. Communicative competence needs a set of competencies i.e. actional competence, linguistic competence, discourse competence, sociocultural competence, and strategic competence. These competencies could not be separated and support each other which are realized through four language skills, i.e. listening, speaking, reading, and writing.Teachers are encourage to teach language using the four language skills in an integrated manner.Â ABSTRAKÂ Proses pembelajaran bahasa Inggris dikemas untuk mengembangkan kemampuan peserta didik menggunakan bahasa Inggris dalam kehidupan sehari-hari. Kegiatan pembelajaran dan penilaian merupakan proses terpadu, artinya penilaian dilakukan ketika kegiatan pembelajaran berlangsung. Berdasarkan kajian pada dokumen Kurikulum Tingkat Satuan Pendidikan (KTSP), bahwa pada umumnya kegiatan penilaian mata pelajaran Bahasa Inggris dirancang sebagai komponen lepas dari kegiatan pembelajaran dan terkesan formal. Di samping itu, kemampuan guru merancang tugas-tugas penilaian juga beragam yang berdampak pada kualitas hasil belajar peserta didik. Memperhatikan kondisi ini, dipandang perlu untuk mengembangkan model penilaian mata pelajaran Bahasa Inggris yang dapat dijadikan acuan bagi guru untuk mengembangkan kurikulum sekolah. Bahasa merupakan alat untuk berkomunikasi secara lisan dan tulis. Kompetensi berkomunikasi merupakan kemampuan seseorang untuk berkomunikasi baik secara lisan maupun tertulis dalam berkomunikasi. Untuk dapat berkomunikasi diperlukan seperangkat kompetensi lainnya: tindak bahasa, kebahasaan, pembentuk wacana, sosio kultural, dan strategi. Kompetensi-kompetensi tersebut merupakan satu kesatuan yang tidak dapat dipisahkan dan saling mendukung yang diwujudkan dalam keterampilan berbahasa, yaitu mendengarkan, berbicara, membaca, dan menulis